Modeled and Measured Carbon Isotopic Composition and Petrographically Estimated Binder-Aggregate Ratio—Recipe for Binding Material Dating?. Issue 3 (June 2019) - Michalska, Danuta; Pawlyta, Jacek
ABSTRACT: This paper presents the results of radiocarbon ( 14 C) dating of bulk mortars and reports an attempt of implementation of the knowledge about the isotopic fractionation, based on δ 13 C measurements, to make the age correction for mortars, together with verification of such correction based on the percentage estimation of carbonate components, namely binder and aggregate. To evaluate the variability of isotopic fractionation during CO2 absorption by mortar, dependent on the climatic and environmental conditions, and the type of mortar, the δ 13 C measurements have been performed for the mortars from Sussita (Golan Heights). Such measurements were also made for fragments of natural carbonate rocks and for mortars produced in the laboratory from the same substrate. We propose the recipe for mortars age estimation.